What's Under a Plastic Strip?: Hidden Urban Biodiversity in the Beijing Metropolitan Area, China - Su, Z.; Huang, D.; Omar, Y.; Ren, L.; Alonso-Zarazaga, M.; Majer, Jonathan; Zhang, R. (The Coleopterists Society, 2012)
This paper reports on the remarkable results we achieved with a novel, inexpensive collecting method, i.e. band-shelter trapping, during a survey conducted in 25 urban parks and greenbelts in the Beijing metropolitan area from April to October during 2007-2009. The trap was made of3-cm wide, opaque, plastic fiber, wrapped around willow tree trunks (Sali.x spp.) at a height of 1.5 m height. Traps were checked every two weeks. We collected a total of 45,074 weevils, of which 817 belong to five species unrecorded from China, i.e., Melanapion mandli (Schubert), Asperogronops inaequalis(Boheman), Dorytomus occallescens (Gyllenhal), Ellescus schoenherri (Faust), and Tachyerges pseudostign1a (Tempere). Moreover, we collected 43,952 individuals of Melanapion nag a (Nakane), Dorytomus alternans Faust, Dorytomus roelofsi Faust, and Dorytomus setosus Zumpt, which are new records for Beijing. The genera Asperogronops Solari and EllescusDejean are newly recorded for China. During their seasonal peak, we frequently and abundantly collected D. setosus and D. roelofsi with band-shelter traps, but never by sweeping, beating, or light trapping methods. A review of the biology of these species shows that all have a short active season and prefer shaded tree trunks. Band-shelter traps appear to effectively capture species with these characteristics and underline the importance of collecting methods that take into account the specific life strategy of target species.